Monitoring Intra-cellular Tacrolimus Concentrations in Solid Organ Transplantation: Use of Peripheral Blood Mononuclear Cells and Graft Biopsy Tissue - Sallustio, Benedetta C. (Frontiers in Pharmacology, 2021)
TTacrolimus is an essential immunosuppressant for the prevention of rejection in solid organ transplantation. Its low therapeutic index and high pharmacokinetic variability necessitates therapeutic drug monitoring (TDM) to individualise dose. However, rejection and toxicity still occur in transplant recipients with blood tacrolimus trough concentrations (C0) within the target ranges. Peripheral blood mononuclear cells (PBMC) have been investigated as surrogates for tacrolimus’ site of action (lymphocytes) and measuring allograft tacrolimus concentrations has also been explored for predicting rejection or nephrotoxicity. There are relatively weak correlations between blood and PBMC or graft tacrolimus concentrations. Haematocrit is the only consistent significant (albeit weak) determinant of tacrolimus distribution between blood and PBMC in both liver and renal transplant recipients. In contrast, the role of ABCB1 pharmacogenetics is contradictory. With respect to distribution into allograft tissue, studies report no, or poor, correlations between blood and graft tacrolimus concentrations. Two studies observed no effect of donor ABCB1 or CYP3A5 pharmacogenetics on the relationship between blood and renal graft tacrolimus concentrations and only one group has reported an association between ABCB1 polymorphisms and hepatic graft tacrolimus concentrations. Several studies describe significant correlations between in vivo PBMC tacrolimus concentrations and ex vivo T-cell activation or calcineurin activity. Older studies provide evidence of a strong predictive value of PBMC C0 and allograft tacrolimus C0 (but not blood C0) with respect to rejection in liver transplant recipients administered tacrolimus with/without a steroid. However, these results have not been independently replicated in liver or other transplants using current triple maintenance immunosuppression. Only one study has reported a possible association between renal graft tacrolimus concentrations and acute tacrolimus nephrotoxicity. Thus, well-designed and powered prospective clinical studies are still required to determine whether measuring tacrolimus PBMC or graft concentrations offers a significant benefit compared to current TDM.